2013
DOI: 10.1590/s1984-92302013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Do auge à retração: análise de um dos estágios de construção do ensino de Administração pública no Brasil (1966-1982)

Abstract: A história do ensino na graduação em Administração Pública (AP) no país ainda carece de sistematização, dada a diminuta quantidade de estudos descritivos e de investigações analíticas do tema, como as teses de Fischer (1984), Coelho (2006), Nicolini (2007) e, tangencialmente, artigos ou relatórios de pesquisa. Defronte dessa lacuna, o objetivo deste trabalho é tanto propor uma periodização para tal ensino no Brasil, como contribuir com a descrição e análise de um dos seus ciclos ou estágios de construção. Meto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
4
0
4
Order By: Relevance
“…PNTE allowed Brazilian academics and international researchers to study and exchange experiences on management in international institutions. As this study relates the program to the development of higher education courses in management and understands the design of these elements for public administration, it joins other works who have discussed the formation of this field in the country (Alcadipani and Bertero, 2012;Barros and Carrieri, 2013;Coelho and Nicolini, 2013). After selecting the project as the research object and delimiting the time frame, the first analysis of the documents related to the program was performed.…”
Section: Methods and Objectmentioning
confidence: 99%
See 2 more Smart Citations
“…PNTE allowed Brazilian academics and international researchers to study and exchange experiences on management in international institutions. As this study relates the program to the development of higher education courses in management and understands the design of these elements for public administration, it joins other works who have discussed the formation of this field in the country (Alcadipani and Bertero, 2012;Barros and Carrieri, 2013;Coelho and Nicolini, 2013). After selecting the project as the research object and delimiting the time frame, the first analysis of the documents related to the program was performed.…”
Section: Methods and Objectmentioning
confidence: 99%
“…New necessities emerged in the scope of government management. We see the decline of courses focused on the specificity of public management and the hegemony of business management (Fischer, 1984;Coelho and Nicolini, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O percurso histórico da administração pública, como relatado em grande parte da bibliografia comumente utilizada (BARROS, 2017;COELHO, 2006COELHO, , 2019NICOLINI, 2013NICOLINI, , 2014SILVA, 1954SILVA, , 1958 se inicia com a criação da primeira escola de administração pública, sendo esta, resultado de uma parceria que intentava implantar este curso no Brasil. Esta narrativa, bastante delineada, agora pretende tomar outros rumos, apontando existências menos demarcadas, mas que podem ser identificadas nos registros dos arquivos históricos, compondo o agenciamento que formaram os saberes públicoadministrativos no Brasil.…”
Section: Introductionunclassified
“…This research found that not only was the U.S. government interested in the implementation of management education in Brazil, but that U.S. foundations also participated in this process. Archived documents from Michigan State University (MSU) indicate that FGV EAESP was designed as a central disseminator of management teaching in Brazil, an aspect that was also highlighted by Coelho & Nicolini (2013). The school sought to influence the expansion of management education in southern Brazil through UFRGS, and in the northeast through UFBA at the same time, some studies indicate that the creation of management education in Brazil occurred in opposition to the influence of the U.S. and the FGV, as shown by Barros and Carrieri (2013) in the case of UFMG.…”
Section: Introductionmentioning
confidence: 99%